Peningkatan Komitmen Terhadap Profesi Melalui Penguatan Kepribadian, Dan Pemberdayaan Guru, Dimediasi Oleh Kepuasan Kerja - Puspasari, Yanthi; Hidayat, Rais; Wulandari, Dian (JURNAL MANAJEMEN PENDIDIKAN, 2025)
INCREASING COMMITMENT TO THE PROFESSION THROUGH PERSONALITY STRENGTHENING, AND TEACHER EMPOWERMENT, MEDIATED BY JOB SATISFACTIONIn general, this research aims to find strategies and ways to increase Commitment to the Profession in Permanent Teachers of Private Elementary School Foundations in Cipayung District, East Jakarta so that it can become input and recommendations for related parties, namely teachers, school principals, school administrators, and education authorities. Apart from that, we also found a new synthesis regarding commitment to the profession, personality, empowerment and job satisfaction. This research was conducted at the private elementary school level because private teachers have a commitment that is certainly different from civil servant teachers. This research uses quantitative research with a path analysis approach, which is a process of finding knowledge that uses data in the form of numbers as a tool to find information about what we want to know. The population in this study were private elementary school teachers with non-GTY status who taught in Cipayung District, East Jakarta. The population is 278 teachers from 10 private elementary schools in the Cipayung sub- district, East Jakarta. Of the 278 permanent foundation teachers at private elementary schools in Cipayung sub-district, East Jakarta, 165 non - GTY people will be sampled. This study found that Personality has a significant effect on teacher professional commitment with a path coefficient of 3.624 (p-value 0.01). Empowerment also contributes significantly with a path coefficient of 4.317 (p- value 0.01), and job satisfaction shows a significant effect with a path coefficient of 2.732 (p-value 0.01). The indirect effect of personality and empowerment on teacher professional commitment is mediated by job satisfaction, each with a coefficient of 0.2095 and 0.2769 indicating an important role of job satisfaction as a mediator. The results of the research show that personality has a direct and very  significant  positive  effect  on  commitment  to the profession through job  satisfaction  so  that strengthening  personality  through  job  satisfaction  can  indirectly  increase  commitment  to  the profession and empowerment has an indirect effect on commitment to the profession through job satisfaction, thereby strengthening empowerment. Through job satisfaction it can indirectly increase commitment to the profession.